(untitled) (AYUSHDHARA, 2021)
Sandhigata Vata is Vatapradhana Vyadhi, which needs a specific target of therapeutic intervention to slow down the process of Dhatu Kshaya and to pacify Vata. We can correlate Sandhigata Vata with osteoarthritis (OA) on the basis of clinical features. OA is defined as a chronic joint disorder with progressive softening and disintegration of articular cartilage and bone at joint margin called osteophytes and capsular fibrosis. Matra Vasti of Panchtikta Guggulu Ghrita is effective in the management of Sandhivata. Aim: To evaluate the efficacy of Matra Vasti of Panchtikta Guggulu Ghrita in the management of Sandhigata Vata (Osteoarthritis). Materials and method: Total 40 patients having signs and symptoms of Sandhivata were selected and randomly divided into two groups. In Group A (n=20), Laksha Guggulu 250mg 2tab for TDS and Group B (n=20) Laksha Guggulu in same dose with 50ml of Matra Vasti of Panchtikta Gugulu Ghrita for 16 days. Results: Statistical analysis of both groups comparison in right knee joint shows that there are no significant results in movement and swelling. In both group comparisons pain shows significant results. Conclusion: Matra Vasti of Panchtikta Guggulu Ghrita provided better results compared to Laksha Guggulu in the management of Sandhivata (Osteoarthritis).